Talent allocation in tournaments: The effect of gender on Italian graduate performance - Carolina Castagnetti; Luisa Rosti (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2007)
We consider the academic performance of Italian university graduates and their labour market position three years after graduation. Our data show that female students outperform male students in academia but are overcome in the labour market. Assuming that academic competition is fair and that individual talent is equally distributed by gender, we suggest that the gender gap evident in degree scores is endogenously due to the greater effort exerted by female students. The rationale for this is that academic tournaments are uneven by gender due to the higher labour market incremental returns to female graduates. In other words, we reconciliate the previous empirical evidence by suggesting and verifying that female students on average engage in a stronger signalling activity (so called screening hypothesis).
Keywords: 330; educational economics; rate of return; Absolventen; Humankapital; Geschlecht; Bildungsertrag; Bildungsökonomik; Schätzung; Italien